Observable player behaviours and playing performance following helmet strikes in elite cricket - Nicholas Peirce; Luke Goggins; Patrick O'Halloran (BMJ Open Sport & Exercise Medicine)
Objectives Investigate the observable player behaviours and features of both concussive (HS-C) and non-concussive (HS-NC) helmet strikes and describe their impact on playing performance.Methods Elite male cricketers sustaining helmet strikes between the 2016 and 2018 seasons were identified by the England and Wales Cricket Board. Medical records identified players sustaining a concussion and those in whom concussion was excluded. Retrospective cohort analysis was performed on batting and bowling performance data available for these players in the 2 years prior to and 3 months post helmet strike. Video analysis of available incidents was conducted to describe the characteristics of the helmet strike and subsequent observable player behaviours. The HS-C and HS-NC cohorts were compared.Results Data were available for 194 helmet strikes. 56 (29%) resulted in concussion. No significant differences were seen in playing performance in the 3 months post concussive helmet strike. However, a significant decline in batting performance was seen in this period in the HS-NC group (p<0.001).Video features signifying motor incoordination were most useful in identifying concussion post helmet strike, however, typical features suggesting transient loss of consciousness were not seen. Features such as a longer duration pause prior to the batsman resuming play and the level of concern shown by other players were also useful features.Conclusion HS-NC may be more significant for player performance than previously thought. Guidance for using video replay to identify concussion in cricket may need to be modified when compared with other field sports.